Lending credence: motivation, trust, and organic certification - Steve Holland (Agricultural and Food Economics, 2016)
The information asymmetries inherent in credence goods have typically led economists to conclude these markets require well-defined quality standards and third-party verification that producers are meeting those standards. Nonetheless, many producers of credence goods appear to be opting out of certification. Why? This paper builds in previous research and develops a theoretical framework to think about how producers' motivation and relationships with consumers affect the necessity and effectiveness of certification. I find the degree to which a consumer trusts the producer of a credence good and the certification standard that governs it and the degree to which the producer is motivated to produce a good of a certain quality both have important effects on certification-based regulation.
Keywords: 330; Credence goods; Organic food; Certification; Agriculture; Trust; Intrinsic motivation